Наследие M. П. Драгоманова: централизм, самоуправление и региональная идентичность славянства - Задорожнюк, И. E.; Лаврик, Э. Г. (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Dragomanow, Russian, Ukrainian and European thinker, applied his abstract ideas to the practical issue of nationality in the 19th century. In his research into the problems of ethnic and regional identity he created a kind of political philosophy of social and national integration that corresponded with the main trends of the 19th century. The essence of this philosophy is the idea of a ‘bunch’ – social self-government which was to become the principle of the whole organizational structure of society. In the 20th century, in the era of strict centralization this idea could be neither applied nor even recognized. Dragomanow was among the first to formulate the problem of European regional identity. At present, when the continent of Europe is divided into three regions: the consolidatingWestern Europe, the disintegrating East Europe (the former USSR countries), and Central Europe emerging as a region, the above-mentioned ideas assume new meaning. Dragomanow’s model that combines the ethnic, cultural, political and economic element in individual countries and regions with the analysis of optimum combinations of self-government and centralization deserves close attention.